2011
DOI: 10.1002/bem.20647
|View full text |Cite
|
Sign up to set email alerts
|

No effects of pulsed electromagnetic fields on expression of cell adhesion molecules (integrin, CD44) and matrix metalloproteinase‐2/9 in osteosarcoma cell lines

Abstract: Pulsed electromagnetic fields (PEMF) could enhance the cytocidal effects of chemotherapeutic drugs on malignant tumor cell lines, but metastasis effects of PEMF on tumor cells have not been investigated. We investigated the effects of PEMF exposure on the expression levels of some metastasis-related molecules, including integrin α subunits (α1, α2, α3, α4, α5, α6, αv), integrin β subunits (β1, β2, β3, β4), CD44, and matrix metalloproteinase-2/9 (MMP-2/9) in four human osteosarcoma cell lines (HOS, MG-63, SAOS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…The possibility of PEMF affecting the intracellular microenvironment of LM8 cells has been previously raised (10,12); thus, we evaluated whether PEMF would accelerate the pharmacological activity of doxorubicin. In this study, the doxorubicin-treated cells immediately after PEMF stimulation for 1 h did not change regarding cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The possibility of PEMF affecting the intracellular microenvironment of LM8 cells has been previously raised (10,12); thus, we evaluated whether PEMF would accelerate the pharmacological activity of doxorubicin. In this study, the doxorubicin-treated cells immediately after PEMF stimulation for 1 h did not change regarding cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al (24) have shown no effects of pulsed EMF on the expression of another CAM, integrin, in osteosarcoma cell lines. Further studies should be performed to verify the findings of this study, including new methods for P-selectin detection in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…The spectra Ω nκ of the problem (62), (CS1) - (CS4), and also of the equivalent problem (66) for the dielectric layer with the induced piecewise continuous permittivity at the frequencies nκ of excitation and generation, consist of not more than countable sets of isolated points, without accumulation points in the finite part of each of the surfaces H nκ , n = 1, 2, 3. The resolvents of the spectral problems at these points are poles of finite order.…”
Section: Theoremmentioning
confidence: 99%
“…Although extremely low electromagnetic fields have been shown to exert beneficial effecets on cartilage tissue (65,66), Lin and Lin investigated the effect of pulsed EMF exposure on osteoblast cells, associated with decreased proliferation and mineralization (67). Okudan, Suslu and co-workers reported the influences of 50 Hz and 0 Hz (static) electric fields (EF), on intact rat bones, as evaluated by dual energy X-ray absorbtion (DEXA) measurements on bone content and density when the animals were continuously exposed in utero and neonatally to EFs.…”
Section: Effects On Osteogenesis and Chondrogenesismentioning
confidence: 99%
See 1 more Smart Citation